Pengaruh Pendekatan Pembelajaran Socio-Scientific Issue Terhadap Kemampuan Literasi Sains Kimia Peserta Didik - Nuria Hikami; Yayuk Andayani; I Nyoman Loka (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The purpose of this study is to determine the effect of the Socio-Scientific Issue (SSI) teaching approach on the chemical science literacy skills of students at MA NW Kembang Kerang. The indicators of science literacy skills measured include the ability to explain scientific phenomena, identify scientific problems, and use evidence in a scientific manner. This research utilizes a Quasi-Experiment design with a pre-test and post-test control group design, conducted in class XI at MA NW Kembang Kerang, involving 41 students. The control class (XI MIPA 1) was taught conventionally, while the experimental class (XI MIPA 2) used the Socio-Scientific Issue teaching approach. Data on chemical science literacy were collected using a test instrument administered before and after the teaching process. The data were analyzed using the N-Gain test and used to draw conclusions. The results of the study show that the SSI teaching approach has an effect on students' chemical science literacy, based on the t-test results where thitung > ttabel. The increase in chemical science literacy in the experimental class is categorized as moderate (N-Gain = 0.60), while the control class is in the low category (N-Gain = 0.28). It is expected that these results can assist both teachers and students in chemistry learning that connects school learning with contextual issues in daily life.